The application of FAPI-targeted theranostics in pancreatic cancer: a narrative review. Issue 2 (8th June 2022) - Liu, Meixi; Hacker, Marcus; Huo, Li; Li, Xiang
Abstract : Pancreatic cancer is one of the most lethal malignancies in the world. Cancer-associated fibroblasts are one of the main components of tumor microenvironment in pancreatic cancer and play an essential role in tumor progression. Fibroblast activation protein that is expressed in specific subtypes of cancer-associated fibroblasts promotes tumor growth and is related to poor survival. Recent researches have preliminarily demonstrated a promising potential of radiopharmaceuticals targeting fibroblast activation protein in diagnosis and therapy of pancreatic cancer. This article comprehensively reviews the current development and clinical translation of fibroblast activation protein inhibitor-targeting radiopharmaceuticals in pancreatic cancer and provides significant perspectives for future investigations.